PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI.IS SMAN 3 SIJUNJUNG TAHUN PELAJARAN 2013/2014 - Ustaza, Qori’a Nur; Rahmi, Rahmi; Mardiyah, Ainil (Pendidikan Matematika, 2013)
This research is motivated by the studentâs understanding of mathematical concepts SMAN 3 Sijunjung is low. Low school spirit towards learning mathematics cause less serious students in the course. This sstudy aims to determine whether studentâs understanding of mathematical concepts by implementing a strategy index card match better than the studentâs understanding of mathematical concepts by applying conventional teaching class XI.IS SMAN 3 Sijunjung 2013-2014 school year. This type of research is experimental. Population is all students in grade 3 SMAN XI.IS Sijunjung 2013-2014 school year. Technique of random sampling, XI.IS.1 as experimental class and XI.IS.2 as control class. Research insrument is the ultimate test with the reliabilitation of 0,99. Because 0,99Â then the matter of the final test has high reliability. Test students understanding of mathematical concepts experimental class was 73,77 with a standard deviation of 21,22 and 59,84 with the control class is standart deviation of 23,13. Hypothesis testing using t-test of the one part, obtained Â > is 2,22 > 1,671. This means the hypothesis is accepted at the level of 95% can be con be concluded student understanding of mathematical concepts by implementing a strategy index card match better than the students understanding by applying conventional learning.